129 HFOPDE, chapter 5.3.1

 129.1 Problem 1
 129.2 Problem 2
 129.3 Problem 3
 129.4 Problem 4
 129.5 Problem 5
 129.6 Problem 6
 129.7 Problem 7
 129.8 Problem 8

_______________________________________________________________________________________

129.1 Problem 1

problem number 1040

Added April 1, 2019.

Problem Chapter 5.3.1.1, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\)

\[ a w_x + b w_y = (c e^{\lambda x}+s e^{\mu y}) w + k e^{\nu x} \]

Mathematica

\[ \left \{\left \{w(x,y)\to e^{\frac{c e^{\lambda x}}{a \lambda }+\frac{s e^{\mu y}}{b \mu }} \left (\int _1^x \frac{k \exp \left (-\frac{s e^{\mu \left (\frac{b (K[1]-x)}{a}+y\right )}}{b \mu }-\frac{c e^{\lambda K[1]}}{a \lambda }+\nu K[1]\right )}{a} \, dK[1]+c_1\left (y-\frac{b x}{a}\right )\right )\right \}\right \} \]

Maple

\[ w \left ( x,y \right ) = \left ( \int ^{x}\!{\frac{k}{a}{{\rm e}^{{\frac{1}{a\lambda \,b\mu } \left ( -as\lambda \,{{\rm e}^{{\frac{\mu \, \left ( ya-b \left ( x-{\it \_a} \right ) \right ) }{a}}}}+\mu \,b \left ( a\lambda \,{\it \_a}\,\nu -c{{\rm e}^{\lambda \,{\it \_a}}} \right ) \right ) }}}}{d{\it \_a}}+{\it \_F1} \left ({\frac{ya-bx}{a}} \right ) \right ){{\rm e}^{{\frac{{{\rm e}^{\lambda \,x}}cb\mu +as\lambda \,{{\rm e}^{\mu \,y}}}{a\lambda \,b\mu }}}} \]

_______________________________________________________________________________________

129.2 Problem 2

problem number 1041

Added April 1, 2019.

Problem Chapter 5.3.1.2, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\)

\[ a w_x + b w_y = c e^{\alpha x+\beta y} w+ k e^{\gamma x} \]

Mathematica

\[ \left \{\left \{w(x,y)\to e^{\frac{c e^{\alpha x+\beta y}}{a \alpha +b \beta }} \left (\int _1^x \frac{k \exp \left (\gamma K[1]-\frac{c e^{\frac{b \beta (K[1]-x)}{a}+\alpha K[1]+\beta y}}{a \alpha +b \beta }\right )}{a} \, dK[1]+c_1\left (y-\frac{b x}{a}\right )\right )\right \}\right \} \]

Maple

\[ w \left ( x,y \right ) = \left ( \int ^{x}\!{\frac{k}{a}{{\rm e}^{{\frac{1}{a\alpha +b\beta } \left ( -c{{\rm e}^{{\frac{\beta \, \left ( ya-b \left ( x-{\it \_a} \right ) \right ) +{\it \_a}\,a\alpha }{a}}}}+{\it \_a}\,\gamma \, \left ( a\alpha +b\beta \right ) \right ) }}}}{d{\it \_a}}+{\it \_F1} \left ({\frac{ya-bx}{a}} \right ) \right ){{\rm e}^{{\frac{c{{\rm e}^{\alpha \,x+\beta \,y}}}{a\alpha +b\beta }}}} \]

_______________________________________________________________________________________

129.3 Problem 3

problem number 1042

Added April 1, 2019.

Problem Chapter 5.3.1.3, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\)

\[ a e^{\lambda x} w_x + b e^{\beta x} w_y = c e^{\gamma y} w+ s e^{\mu x+\delta y} \]

Mathematica

\[ \left \{\left \{w(x,y)\to \exp \left (\int _1^x \frac{c \exp \left (-\frac{b \gamma \left (e^{x (\beta -\lambda )}-e^{(\beta -\lambda ) K[1]}\right )}{a (\beta -\lambda )}-\lambda K[1]+\gamma y\right )}{a} \, dK[1]\right ) \left (\int _1^x \frac{s \exp \left (-\text{Integrate}\left [\frac{c \exp \left (-\frac{b \gamma \left (e^{x (\beta -\lambda )}-e^{(\beta -\lambda ) K[1]}\right )}{a (\beta -\lambda )}-\lambda K[1]+\gamma y\right )}{a},\{K[1],1,K[2]\},\text{Assumptions}\to \text{True}\right ]-\frac{b \delta \left (e^{x (\beta -\lambda )}-e^{(\beta -\lambda ) K[2]}\right )}{a (\beta -\lambda )}+(\mu -\lambda ) K[2]+\delta y\right )}{a} \, dK[2]+c_1\left (\frac{b e^{x (\beta -\lambda )}}{a (\lambda -\beta )}+y\right )\right )\right \}\right \} \]

Maple

\[ w \left ( x,y \right ) = \left ( \int ^{x}\!{\frac{s}{a}{{\rm e}^{{\frac{1}{a \left ( -\beta +\lambda \right ) } \left ( -c \left ( -\beta +\lambda \right ) \int \!{{\rm e}^{{\frac{{{\rm e}^{{\it \_a}\, \left ( \beta -\lambda \right ) }}\gamma \,b-{{\rm e}^{x \left ( \beta -\lambda \right ) }}\gamma \,b+a \left ( \beta -\lambda \right ) \left ( -\lambda \,{\it \_a}+\gamma \,y \right ) }{ \left ( \beta -\lambda \right ) a}}}}\,{\rm d}{\it \_a}-{{\rm e}^{{\it \_a}\, \left ( \beta -\lambda \right ) }}b\delta +{{\rm e}^{x \left ( \beta -\lambda \right ) }}b\delta -a \left ( -\beta +\lambda \right ) \left ( \lambda \,{\it \_a}-\mu \,{\it \_a}-\delta \,y \right ) \right ) }}}}{d{\it \_a}}+{\it \_F1} \left ({\frac{-b{{\rm e}^{x \left ( \beta -\lambda \right ) }}+ay \left ( \beta -\lambda \right ) }{ \left ( \beta -\lambda \right ) a}} \right ) \right ){{\rm e}^{\int ^{x}\!{\frac{c}{a}{{\rm e}^{{\frac{{{\rm e}^{{\it \_a}\, \left ( \beta -\lambda \right ) }}\gamma \,b-{{\rm e}^{x \left ( \beta -\lambda \right ) }}\gamma \,b+a \left ( \beta -\lambda \right ) \left ( -\lambda \,{\it \_a}+\gamma \,y \right ) }{ \left ( \beta -\lambda \right ) a}}}}}{d{\it \_a}}}} \]

_______________________________________________________________________________________

129.4 Problem 4

problem number 1043

Added April 1, 2019.

Problem Chapter 5.3.1.4, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\)

\[ a e^{\beta x} w_x + (b e^{\gamma x} +c e^{\lambda y})w_y = s w+k e^{\mu x+\delta y} \]

Mathematica

\[ \text{Failed} \]

Maple

\[ w \left ( x,y \right ) = \left ( \int ^{x}\!{\frac{k}{a} \left ({\frac{1}{a} \left ( \lambda \,c\int \!{{\rm e}^{{\frac{-\lambda \,b{{\rm e}^{x \left ( \gamma -\beta \right ) }}-ax\beta \, \left ( -\gamma +\beta \right ) }{ \left ( -\gamma +\beta \right ) a}}}}\,{\rm d}x-c\int \!{{\rm e}^{{\frac{-\lambda \,b{{\rm e}^{{\it \_b}\, \left ( \gamma -\beta \right ) }}-a{\it \_b}\,\beta \, \left ( -\gamma +\beta \right ) }{ \left ( -\gamma +\beta \right ) a}}}}\,{\rm d}{\it \_b}\lambda +{{\rm e}^{-{\frac{ \left ( b{{\rm e}^{x \left ( \gamma -\beta \right ) }}+ay \left ( -\gamma +\beta \right ) \right ) \lambda }{ \left ( -\gamma +\beta \right ) a}}}}a \right ) } \right ) ^{-{\frac{\delta }{\lambda }}}{{\rm e}^{{\frac{-{{\rm e}^{{\it \_b}\, \left ( \gamma -\beta \right ) }}b\beta \,\delta + \left ( s{{\rm e}^{-\beta \,{\it \_b}}}+a{\it \_b}\,\beta \, \left ( -\beta +\mu \right ) \right ) \left ( -\gamma +\beta \right ) }{ \left ( -\gamma +\beta \right ) a\beta }}}}}{d{\it \_b}}+{\it \_F1} \left ({\frac{1}{a\lambda } \left ( -\lambda \,c\int \!{{\rm e}^{{\frac{-\lambda \,b{{\rm e}^{x \left ( \gamma -\beta \right ) }}-ax\beta \, \left ( -\gamma +\beta \right ) }{ \left ( -\gamma +\beta \right ) a}}}}\,{\rm d}x-{{\rm e}^{-{\frac{ \left ( b{{\rm e}^{x \left ( \gamma -\beta \right ) }}+ay \left ( -\gamma +\beta \right ) \right ) \lambda }{ \left ( -\gamma +\beta \right ) a}}}}a \right ) } \right ) \right ){{\rm e}^{-{\frac{s{{\rm e}^{-\beta \,x}}}{a\beta }}}} \]

_______________________________________________________________________________________

129.5 Problem 5

problem number 1044

Added April 1, 2019.

Problem Chapter 5.3.1.5, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\)

\[ a e^{\beta x} w_x + (b e^{\gamma x} +c e^{\lambda y})w_y = s e^{\mu x+\delta y} w + k \]

Mathematica

\[ \text{Failed} \]

Maple

\[ w \left ( x,y \right ) ={\frac{1}{a}{{\rm e}^{{\frac{s}{a}\int ^{x}\! \left ({\frac{1}{a} \left ( \lambda \,c\int \!{{\rm e}^{{\frac{-\lambda \,b{{\rm e}^{x \left ( \gamma -\beta \right ) }}-ax\beta \, \left ( -\gamma +\beta \right ) }{ \left ( -\gamma +\beta \right ) a}}}}\,{\rm d}x-c\int \!{{\rm e}^{{\frac{-\lambda \,b{{\rm e}^{{\it \_b}\, \left ( \gamma -\beta \right ) }}-a{\it \_b}\,\beta \, \left ( -\gamma +\beta \right ) }{ \left ( -\gamma +\beta \right ) a}}}}\,{\rm d}{\it \_b}\lambda +{{\rm e}^{-{\frac{ \left ( b{{\rm e}^{x \left ( \gamma -\beta \right ) }}+ay \left ( -\gamma +\beta \right ) \right ) \lambda }{ \left ( -\gamma +\beta \right ) a}}}}a \right ) } \right ) ^{-{\frac{\delta }{\lambda }}}{{\rm e}^{{\frac{-\delta \,b{{\rm e}^{{\it \_b}\, \left ( \gamma -\beta \right ) }}+a{\it \_b}\, \left ( -\gamma +\beta \right ) \left ( -\beta +\mu \right ) }{ \left ( -\gamma +\beta \right ) a}}}}{d{\it \_b}}}}} \left ({\it \_F1} \left ({\frac{1}{a\lambda } \left ( -\lambda \,c\int \!{{\rm e}^{{\frac{-\lambda \,b{{\rm e}^{x \left ( \gamma -\beta \right ) }}-ax\beta \, \left ( -\gamma +\beta \right ) }{ \left ( -\gamma +\beta \right ) a}}}}\,{\rm d}x-{{\rm e}^{-{\frac{ \left ( b{{\rm e}^{x \left ( \gamma -\beta \right ) }}+ay \left ( -\gamma +\beta \right ) \right ) \lambda }{ \left ( -\gamma +\beta \right ) a}}}}a \right ) } \right ) a+\int ^{x}\!{{\rm e}^{{\frac{1}{a} \left ( -{\it \_b}\,a\beta -s\int \! \left ({\frac{1}{a} \left ( \lambda \,c\int \!{{\rm e}^{{\frac{-\lambda \,b{{\rm e}^{x \left ( \gamma -\beta \right ) }}-ax\beta \, \left ( -\gamma +\beta \right ) }{ \left ( -\gamma +\beta \right ) a}}}}\,{\rm d}x-c\int \!{{\rm e}^{{\frac{-\lambda \,b{{\rm e}^{{\it \_b}\, \left ( \gamma -\beta \right ) }}-a{\it \_b}\,\beta \, \left ( -\gamma +\beta \right ) }{ \left ( -\gamma +\beta \right ) a}}}}\,{\rm d}{\it \_b}\lambda +{{\rm e}^{-{\frac{ \left ( b{{\rm e}^{x \left ( \gamma -\beta \right ) }}+ay \left ( -\gamma +\beta \right ) \right ) \lambda }{ \left ( -\gamma +\beta \right ) a}}}}a \right ) } \right ) ^{-{\frac{\delta }{\lambda }}}{{\rm e}^{{\frac{-\delta \,b{{\rm e}^{{\it \_b}\, \left ( \gamma -\beta \right ) }}+a{\it \_b}\, \left ( -\gamma +\beta \right ) \left ( -\beta +\mu \right ) }{ \left ( -\gamma +\beta \right ) a}}}}\,{\rm d}{\it \_b} \right ) }}}{d{\it \_b}}k \right ) } \]

_______________________________________________________________________________________

129.6 Problem 6

problem number 1045

Added April 1, 2019.

Problem Chapter 5.3.1.6, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\)

\[ a e^{\beta x} w_x + b e^{\gamma x+\lambda y} w_y = c e^{\sigma y} w + k e^{\mu x+delta y} + d \]

Mathematica

\[ \text{\$Aborted} \]

Maple

\[ w \left ( x,y \right ) = \left ( \int ^{x}\!{\frac{1}{a} \left ( k \left ({\frac{ \left ( -\gamma +\beta \right ) a}{-b\lambda \,{{\rm e}^{-y\lambda }}{{\rm e}^{x \left ( \gamma -\beta \right ) +y\lambda }}+\lambda \,b{{\rm e}^{{\it \_b}\, \left ( \gamma -\beta \right ) }}+{{\rm e}^{-y\lambda }}a \left ( -\gamma +\beta \right ) }} \right ) ^{{\frac{\delta }{\lambda }}}{{\rm e}^{{\frac{1}{a} \left ( -c\int \! \left ({\frac{ \left ( -\gamma +\beta \right ) a}{-b\lambda \,{{\rm e}^{-y\lambda }}{{\rm e}^{x \left ( \gamma -\beta \right ) +y\lambda }}+\lambda \,b{{\rm e}^{{\it \_b}\, \left ( \gamma -\beta \right ) }}+{{\rm e}^{-y\lambda }}a \left ( -\gamma +\beta \right ) }} \right ) ^{{\frac{\sigma }{\lambda }}}{{\rm e}^{-\beta \,{\it \_b}}}\,{\rm d}{\it \_b}+a{\it \_b}\, \left ( -\beta +\mu \right ) \right ) }}}+d{{\rm e}^{{\frac{1}{a} \left ( -{\it \_b}\,a\beta -c\int \! \left ({\frac{ \left ( -\gamma +\beta \right ) a}{-b\lambda \,{{\rm e}^{-y\lambda }}{{\rm e}^{x \left ( \gamma -\beta \right ) +y\lambda }}+\lambda \,b{{\rm e}^{{\it \_b}\, \left ( \gamma -\beta \right ) }}+{{\rm e}^{-y\lambda }}a \left ( -\gamma +\beta \right ) }} \right ) ^{{\frac{\sigma }{\lambda }}}{{\rm e}^{-\beta \,{\it \_b}}}\,{\rm d}{\it \_b} \right ) }}} \right ) }{d{\it \_b}}+{\it \_F1} \left ( -{\frac{ \left ( -\lambda \,b{{\rm e}^{x \left ( \gamma -\beta \right ) +y\lambda }}+ \left ( -\gamma +\beta \right ) a \right ){{\rm e}^{-y\lambda }}}{\lambda \,b \left ( -\gamma +\beta \right ) }} \right ) \right ){{\rm e}^{\int ^{x}\!{\frac{c{{\rm e}^{-\beta \,{\it \_a}}}}{a} \left ({\frac{ \left ( -\gamma +\beta \right ) a}{-b\lambda \,{{\rm e}^{-y\lambda }}{{\rm e}^{x \left ( \gamma -\beta \right ) +y\lambda }}+\lambda \,b{{\rm e}^{{\it \_a}\, \left ( \gamma -\beta \right ) }}+{{\rm e}^{-y\lambda }}a \left ( -\gamma +\beta \right ) }} \right ) ^{{\frac{\sigma }{\lambda }}}}{d{\it \_a}}}} \]

_______________________________________________________________________________________

129.7 Problem 7

problem number 1046

Added April 1, 2019.

Problem Chapter 5.3.1.7, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\)

\[ a e^{\lambda y} w_x + b e^{\beta x} w_y = c w + s e^{\gamma x} \]

Mathematica

\[ \left \{\left \{w(x,y)\to e^{-\frac{c e^{-\lambda x}}{a \lambda }} \left (\int _1^x \frac{s e^{\frac{c e^{-\lambda K[1]}}{a \lambda }+\gamma K[1]-\lambda K[1]}}{a} \, dK[1]+c_1\left (-\frac{e^{-\lambda x} \left (-a \beta y e^{\lambda x}+a \lambda y e^{\lambda x}+b e^{\beta x}\right )}{a (\beta -\lambda )}\right )\right )\right \}\right \} \]

Maple

\[ w \left ( x,y \right ) = \left ( \int \!{\frac{s}{a}{{\rm e}^{{\frac{c{{\rm e}^{-\lambda \,x}}+ax\lambda \, \left ( \gamma -\lambda \right ) }{a\lambda }}}}}\,{\rm d}x+{\it \_F1} \left ({\frac{-b{{\rm e}^{x \left ( \beta -\lambda \right ) }}+ay \left ( \beta -\lambda \right ) }{ \left ( \beta -\lambda \right ) a}} \right ) \right ){{\rm e}^{-{\frac{c{{\rm e}^{-\lambda \,x}}}{a\lambda }}}} \]

_______________________________________________________________________________________

129.8 Problem 8

problem number 1047

Added April 1, 2019.

Problem Chapter 5.3.1.8, from Handbook of first order partial differential equations by Polyanin, Zaitsev, Moussiaux.

Solve for \(w(x,y)\)

\[ a e^{\lambda y} w_x + b x^{\beta x} w_y = c e^{\gamma x} w + s \]

Mathematica

\[ \text{\$Aborted} \]

Maple

\[ w \left ( x,y \right ) = \left ( \int \!{\frac{s}{a}{{\rm e}^{{\frac{-c{{\rm e}^{ \left ( \gamma -\lambda \right ) x}}-ax\lambda \, \left ( \gamma -\lambda \right ) }{ \left ( \gamma -\lambda \right ) a}}}}}\,{\rm d}x+{\it \_F1} \left ({\frac{ya-b\int \!{x}^{\beta \,x}{{\rm e}^{-\lambda \,x}}\,{\rm d}x}{a}} \right ) \right ){{\rm e}^{{\frac{c{{\rm e}^{ \left ( \gamma -\lambda \right ) x}}}{ \left ( \gamma -\lambda \right ) a}}}} \]